O genocídio da população negra no Brasil: a relação estrutural entre racismo e capitalismo - Alves, Daniel Tadeu (2023)
The objective of this work is to deepen the studies on the relations established between racism and capitalism in the course of history. We seek to decipher the role of racism for the edification of the race category, for the emergence of colonialism and what is its role for the development of social relations of production in capitalist sociability. We researched how the historical, political, economic, cultural and social processes established under the relationship between racism and capitalism engendered the project of anti-black and anti-indigenous genocide in the Brazilian social formation and its determinations for the development of dependent capitalism in Brazil. We propose to discuss the concept of structural racism, its interfaces with the coloniality of power and with the maintenance of the conditions necessary for the development and continuity of capi talism, having the anti-black and anti-indigenous genocide as a substantial strategy. Using by method the dialectical historical materialism, we conducted bibliographic review and analysis of statistical data that would allow us to apprehend the movement Concrete of the reality experi enced by the black population in Brazil. This research identified the existence of a structural and dialectical relationship between racism and capitalism, being the anti-black genocide and its mul tiple expressions, the result of this relationship, which operationalizes the maintenance of the conditions necessary for the development and continuity of Brazilian dependent capitalism. We point out that the overcoming of the capitalist mode of production is intrinsically connected to the anti-racist struggle and the confrontation of the anti-black genocide in its multiple expressions and that the radical apprehension of this reality is a first step towards the construction of a new social order